WTO agreements - Das, Bhagirath Lal (London, 1998)
This companion volume to An Introduction to the WTO Agreements looks at how the WTO agreements represent progress over the GATT rules they have replaced. The author also analyses their deficiencies and imbalances from the point of view of the developing countries.
Keywords: World Trade Organisation